Passivity and Semiconducting Behavior of a High Nitrogen Stainless Steel in Acidic NaCl Solution - Yanxin Qiao; Xiang Cai; Jie Cui; Huabing Li (Advances in Materials Science and Engineering)
The passivity and semiconducting behaviors of a high nitrogen-containing nickel-free stainless steel (HNSS) in 0.05 mol/L H2SO4 + 0.5 mol/L NaCl have been investigated. Results indicated that HNSS offered excellent pitting corrosion resistance in corrosive environments. Three corrosion potential values were observed in potentiodynamic polarization response, indicating the existence of an unstable system. The current transient and Mott-Schottky plots demonstrated that the stability of passive films decreased with the increase of applied potentials. The angle resolved X-ray photoelectron spectrometric results revealed that the primary constituents of passive films formed in 0.05 mol/L H2SO4 + 0.5 mol/L NaCl solution were composed of iron oxides, manganese oxides, Cr2O3, and Cr(OH)3. Meanwhile, it indicated that molybdenum oxides did not exist in the oxide layer, but chloride ions were present in the passive films.